Modelagem estatística para análise de dados imobiliários completos e com censura à esquerda - Estevam, Amanda Cristina (2014)
The real estate market has a key role in the country and counties economy attracting several studies and researches that explains and interpret the numerous transactions performed, and especially to find appropriate ways to define the monetary value. Usually the real estate data modeling is performed through regression models, especially the linear and also the generalized linear models ( Nelder andWedderburn, 1972). Because these data has different characteristics such as heteroscedasticity, non-normality and heterogeneity, the use of these models can suffer limitations, so it is appropriate to use more and more complex models, such as generalized additive models for location, scale and shape GAMLSS (proposed by Rigby & Stasinopoulos (2005), that allows all parameters of the response variable are modeled parametric or non parametric form. In this context and based on a dataset of urban land of São Carlos city in 2005 was estimated the empirical function the value of the land addressing the class of linear models, generalized linear models and the GAMLSS. Alternatively, considering the existence of two types of real estate prices: already sold (observed) and announced (censored), was proposed to the data, using the survival analysis considering censored left and the GAMLSS in the parameter estimation process. A simulation study and a study of local influence was also performed.